The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/3878359
|View full text |Cite|
|
Sign up to set email alerts
|

Study of Serum Anti-Mullerian Hormone in the Diagnosis of Ovarian Reserve Function in Patients with Premature Ovarian Insufficiency

Abstract: Objective. To explore the diagnostic value of serum anti-Mullerian hormone (AMH) for patients with premature ovarian insufficiency (POI) and premature ovarian failure (POF). Methods. Totally, 125 women with menstrual disorder treated in the Obstetrics and Gynecology Department of Ningbo Women & Children Hospital between January 2020 and December 2021 were enrolled. Among them, based on the follicle-stimulating hormone (FSH) level, 54 patients ( 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[21] Another study showed, AMH was 0.69±1.46 ng/mL and estradiol was 3.69±2.82 ng/mL in patients with POI, which was relatable to the present study. [22] In this study, patients had normal puberty, and menarche occurred at ages 11-15, followed by a regular menstrual cycle. Women who presented with oligomenorrhea were younger than patients with infertility.…”
Section: Discussionmentioning
confidence: 76%
“…[21] Another study showed, AMH was 0.69±1.46 ng/mL and estradiol was 3.69±2.82 ng/mL in patients with POI, which was relatable to the present study. [22] In this study, patients had normal puberty, and menarche occurred at ages 11-15, followed by a regular menstrual cycle. Women who presented with oligomenorrhea were younger than patients with infertility.…”
Section: Discussionmentioning
confidence: 76%
“…To date, four studies have reported the usefulness of AMH levels as a predictor of POI. [48][49][50]54 As shown in Table 8, the cut-off values for predicting the onset of POI are low AMH of <8 pmol/L (1.12 ng/mL) at <36 years, 49 low AMH of <1.12 ng/mL at <40 years, 50 and low AMH of <0.83 ng/mL at 18-40 years, 48 respectively. In patients with Turner syndrome, including mosaicism, the cut-off value was low AMH of <5 pmol/L (0.7 ng/mL).…”
Section: Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%